READING HABITS AND THE STUDENTS’ WRITING SKILL AMONG EFL LEARNERS - Setyaningrum, Riya Risqi; Fatmawati, Riryn; Nahdiah, Sirli (Universitas PGRI Sumatera Barat, 2022)
The study aims to find out the reading habits of EFL students to find out the writing skill of students and to find out a significant relationship between students' reading habits and the writing skill of students in the informatics engineering study program UNISLA. The method of study is quantitative with a correlation descriptive design. The data collection is documentation of students’ score in portfolio writing and the questionnaire’s score of reading habits. The instruments of research are the report mark of students’ writing ability and the questionnaire. The finding showed that the value of “r” is 0.41. It means that the correlation between students' reading habits and writing skill between English learners of Informatics Engineering at UNISLA in the academic year 2021/2022 were